2007
DOI: 10.1093/her/cym011
|View full text |Cite
|
Sign up to set email alerts
|

Community development and HIV/STI-related vulnerability among female sex workers in Rio de Janeiro, Brazil

Abstract: The Sonagachi Project of Kolkata, India has been recognized as a model community development and human immunodeficiency virus/sexually transmitted infection (HIV/STI) prevention intervention among female sex workers. Limited research has been conducted regarding its applicability outside the South Asian context. This study sought to document the process and effectiveness of integrating community development activities based on the Sonagachi model into an ongoing HIV/STI peer education program with female sex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 6 publications
1
78
1
1
Order By: Relevance
“…More than half had suffered verbal abuse and more than one third physical abuse, both in the setting of their sex work -by clients and police -and in the domestic context, by intimate partners and family members or other known persons. These findings corroborate other studies such as Pando et al 16 and Kerrigan et al 11 , reporting that 25.9% of female sex workers in Rio de Janeiro suffered discrimination and 15.8% suffered violence related to sex work in the four months prior to the study. The current study's results demonstrate the disproportional burden of violence experienced by female sex workers in Brazil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than half had suffered verbal abuse and more than one third physical abuse, both in the setting of their sex work -by clients and police -and in the domestic context, by intimate partners and family members or other known persons. These findings corroborate other studies such as Pando et al 16 and Kerrigan et al 11 , reporting that 25.9% of female sex workers in Rio de Janeiro suffered discrimination and 15.8% suffered violence related to sex work in the four months prior to the study. The current study's results demonstrate the disproportional burden of violence experienced by female sex workers in Brazil.…”
Section: Discussionsupporting
confidence: 91%
“…More than one-third walked the streets and had worked in the sex trade for three years or less. Kerrigan et al 11 observed a similar profile in another study of sex workers in Rio de Janeiro. The structural components of this profile, rooted in gender and class inequalities, reflect fundamental human rights violations and thus the high vulnerability of these women to violence, margin- alizing them and limiting their opportunities and the capacity to reduce the risks from their sexual activity, including HIV infection.…”
Section: Discussionmentioning
confidence: 55%
“…In a survey of 434 sex workers in Rio de Janeiro, Kerrigan et al 25 found that that social cohesion and mutual aid (measured through eight factors, including: level of group connectedness, caring, and potential for instrumental, emotion and material support) (OR = 1.30; 95%CI 1.02 to 1.66), possession of official documents and access to resources (OR = 1.36, 95%CI 1.11 to 1.65), and participation in community organizations (OR = 1, 56; 95%CI 1.04 to 2.34) were significantly associated with condom use with clients in the last four months. According to Lippman et al 26 , high social cohesion was inversely associated with the number of unprotected sex acts in the week prior to interview (IRR = 0.80; p<0.01), and the women's participation in social networks was associated with a reduced frequency of unprotected sex (IRR = 0.83; p = 0.04).…”
Section: Prostitution Contexts and Their Relation To Hivmentioning
confidence: 99%
“…REV BRAS EPIDEMIOL SEP 2015; 18 SUPPL 1: [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] prostitution has aspects that remain in Brazil's Penal Code. Although the inclusion of "sex workers" in the Brazilian Classification of Occupations by the Ministry of Labor ensures the right to social security and other labor benefits, commercial activities related to prostitution (such as brothels) are illegal, which creates an extremely difficult context for sex workers to work safely.…”
Section: Introductionmentioning
confidence: 99%
“…But they led to very different outcomes. The Sonagachi Project in India is often hailed as one of the success stories of participatory HIV prevention, and is being used as a model project for replication around India and overseas (Blankenship, Friedman, Dworkin & Mantell, 2006;Kerrigan, Telles, Torres, Overs & Castle, 2008;UNAIDS, 2008). It has been successful on several counts: in biomedical terms, it has increased condom use and decreased levels of STIs in the red light districts of West Bengal (Jana et al, 1998;Basu et al, 2004).…”
mentioning
confidence: 99%